Ministry Of Finance Decree No. 381 Of The Year 2018 Amending Decree of the Minister of Finance No. 530 Of The Year 2005 Concerning The Collection Of An Amount For Account Of The Non-Commercial Profession Tax Payable By Lawyers According To The Provision Of Article (71) Of Income Tax Law No. 91 Of the year 2005 = وزارة المالية قرار رقم 381 لسنة 2018 بتعديل قرار وزير المالية رقم 530 لسنة 2005 بشأن تحصيل مبلغ تحت حساب ضريبة المهن غير التجارية المستحقة على المحامين طبقاً لحكم المادة (71) من قانون الضريبة على الدخل رقم 91 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic